Presentation of Keynotes Address 5 Tittle : Global Leadership for World-Class University / Professor Dr. Garry James Clayton - Clayton, Garry James (2010)
Achieving “World Class University” status requires planning, persistence and patience. While perhaps desired by most it can only be accomplished by a small number of what in effect are elite institutions. Recognized by a reputation for excellence a “World Class University” is judged by its peers and the market place on its research, relevance, resourcing, and regulatory regime. Such institutions are primarily focused not on scale of operation but substance of outputs. Providing the inspiration for a “World Class University” are leaders who think both strategically and globally. For them national boundaries are bridges not barriers to the world. They are able to balance effectiveness with efficiency, they ensure that the “right things are done in the right way”. Though based on the identifiable principles of transformational leadership, this balance is not merely the oft quoted ART it is more an ARTFORM. Going beyond traditional university Administration, Research and Teaching these leaders; Aim clear and high, Recruit requisite talent, Talk through the vision, Formulate inspirational implementation plans, Orientate the organization, Resource sufficiently, and constantly Monitor both the outcomes and environment). Such leadership is not inherent in any individual; rather it is a consciously practiced process that marks out the successful high fliers from the struggling hard workers.